Level of Knowledge, Attitude, and Family Support in Pulmonary TB Patients in Compliance with Taking Anti-Tuberculosis Drugs - Pramugita, Lisa; Sofiana, Liena; Oktaviana, Ardyawati Wira (Insights in Public Health Journal, 2025)
Background: Tuberculosis (TB) is a disease caused by the bacteria Mycobacterium tuberculosis. TB is one of the top 13 causes of death in the world. This research aims to determine the level of knowledge, attitudes and family support for pulmonary TB sufferers in compliance with taking OAT in the Depok III Health Center working area, Sleman Regency. Methods: This research is descriptive research with quantitative descriptive methods. This research was conducted at the Depok III Community Health Center, Sleman Regency with a sample of 33 respondents. The sampling technique uses total sampling and univariate analysis to describe each research variable. Results: This study showed that of the 33 respondents with compliance in taking medication in the compliant category of 75.8%, the level of knowledge of pulmonary TB sufferers regarding compliance with taking OAT was highest in respondents with good knowledge and compliance with taking medication (42.4%), attitude Pulmonary TB sufferers who adhere most to taking OAT have a positive attitude and adhere to taking medication (39.4%). Meanwhile, family support for pulmonary TB sufferers in adherence to taking OAT was highest among respondents with good family support and adherents to taking medication (45.5%). Conclusions: Based on the research results, it can be concluded that the level of adherence to taking OAT in pulmonary TB sufferers is (75.8%) adherent to taking medication. Description of the knowledge of pulmonary TB sufferers regarding adherence to taking OAT. Most of them have good knowledge and are obedient to taking OAT. The attitude of pulmonary TB sufferers in taking OAT is mostly positive, but only 39.4% adhere to taking medication. Likewise, with the support of families of pulmonary TB sufferers in compliance with taking OAT, the majority have good family support and are adherent to taking medication.